A correlation of magnetic properties with material density for soft magnetic composite cores. Issue 3 (5th May 2015) - Demenko, Ivo Doležel, Kay Hameyer, Wojciech Pietrowski; Krzysztof Zawirski, Andrzej; Ślusarek, Barbara; Szczyglowski, Jan; Chwastek, Krzysztof; Jankowski, Bartosz
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the relationships between processing conditions and magnetic properties of cores made of Soft Magnetic Composite (SMC) Somaloy 500. Design/methodology/approach – The effects of compaction pressure and hardening temperature may be combined considering SMC density. This quantity may be chosen for optimization of properties of ready-made cores. In order to describe hysteresis loops the phenomenological model based on hyperbolic tangent transformation is applied. Findings – SMC density affects substantially the shape of hysteresis loop. The paper provides a number of charts useful for checking how the parameters of the hysteresis model are affected. Research limitations/implications – The present study considers just one composition of the SMC and one type of lubricant. Future research shall be devoted to verification of the approach on a wider class of SMCs. Practical implications – Material density may be a relevant quantity in optimization of magnetic properties of ready-made SMC cores. The simple hysteresis model based on the, "effective field" concept and Takács' idea of hyperbolic tangent transformation may be useful for description of hysteresis curves of SMC cores. Model parameters are sensitive against variations of material density. Originality/value – The results of the analysis may be useful for designers of magnetic circuits made of SMCs.